Walking Exercise Therapy Effects on Lower Extremity Skeletal Muscle in Peripheral Artery Disease. Issue 12 (11th June 2021) - McDermott, Mary M.; Dayanidhi, Sudarshan; Kosmac, Kate; Saini, Sunil; Slysz, Joshua; Leeuwenburgh, Christiaan; Hartnell, Lisa; Sufit, Robert; Ferrucci, Luigi
Abstract : Walking exercise is the most effective noninvasive therapy that improves walking ability in peripheral artery disease (PAD). Biologic mechanisms by which exercise improves walking in PAD are unclear. This review summarizes evidence regarding effects of walking exercise on lower extremity skeletal muscle in PAD. In older people without PAD, aerobic exercise improves mitochondrial activity, muscle mass, capillary density, and insulin sensitivity in skeletal muscle. However, walking exercise increases lower extremity ischemia in people with PAD, and therefore, mechanisms by which this exercise improves walking may differ between people with and without PAD. Compared with people without PAD, gastrocnemius muscle in people with PAD has greater mitochondrial impairment, increased reactive oxygen species, and increased fibrosis. In multiple small trials, walking exercise therapy did not consistently improve mitochondrial activity in people with PAD. In one 12-week randomized trial of people with PAD randomized to supervised exercise or control, supervised treadmill exercise increased treadmill walking time from 9.3 to 15.1 minutes, but simultaneously increased the proportion of angular muscle fibers, consistent with muscle denervation (from 7.6% to 15.6%), while angular myofibers did not change in the control group (from 9.1% to 9.1%). These findings suggest an adaptive response to exercise in PAD that includes denervation and reinnervation, an adaptive process observed in skeletal muscle of people without PAD during aging. Small studies have not shown significant effects of exercise on increased capillary density in lower extremity skeletal muscle of participants with PAD, and there are no data showing that exercise improves microcirculatory delivery of oxygen and nutrients in patients with PAD. However, the effects of supervised exercise on increased plasma nitrite abundance after a treadmill walking test in people with PAD may be associated with improved lower extremity skeletal muscle perfusion and may contribute to improved walking performance in response to exercise in people with PAD. Randomized trials with serial, comprehensive measures of muscle biology, and physiology are needed to clarify mechanisms by which walking exercise interventions improve mobility in PAD.